Peningkatan Populasi, Pertumbuhan dan Serapan Nitrogen Tanaman Kedelai dengan Pemberian Azotobacter Penghasil Eksopolisakarida - Hindersah, Reginawanti; Rostini, Neni; Harsono, Arief; Nuryani, dan (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
Nitrogen-fixing Azotobacter is widely used as biofertilizer in sustainable agriculture. The bacteria produce exopolysaccharide which might have a significant role in enhancing soybean nitrogen uptake and growth. The objective of this research was to obtain growth media of Exopolysaccharide–producing Azotobacter; and increase shoot and root growth as well as nitrogen uptake of soybean var. Anjasmoro at early vegetative phase following inoculation of Azotobacter chroococcum liquid. Research consist of two phase, 1) determination of organic-based media for A. chroococcum liquid inoculant production, and 2) pot experiment for application of liquid inoculant on soybean.  The first experiment was performed  in a series of  batch fermenter consisted of several organic media for 72 hours.  The second experiment was set in completely randomized design consisted of three density of liquid inoculant. The results verified that the best media which induced exopolysachharide production of A. chroococcum was 1% molase enriched with 0.1% NH4Cl. Liquid inoculant clearly enhanced population of Azotobacter in soybean rhizosphere, plant height, roots dry weight and N uptake of 21 day old soybean. This research implied that A. chroococcum might be used as biofertilizer at early growth of soybean. Keywords: Azotobacter chroococcum, biofertilizer, liquid inoculat